2016
DOI: 10.1016/j.jallcom.2016.06.280
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution and competitive reaction behavior of Ti-B4C system under solid-state sintering

Abstract: By using experimental investigations and theoretical calculations, microstructural evolution and competitive reaction behavior of Ti-B 4 C system under solid-state sintering is confirmed. Firstly, B 4 C decomposes into B and C atoms followed by diffusing into Ti side immediately, and TiB whiskers form in Ti matrix. Then, Ti atoms diffuse into B 4 C via vacancies left by the diffused B and C atoms, leading TiB 2 and carbon substance to form in B 4 C side. Subsequently, reaction product carbon diffuses into Ti s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…However, TiC and TiB diffraction peaks appeared in the diffraction patterns of TMCs consolidated at 1000 °C as shown in Figure 2 b, while the XRD patterns of TiB 2 peaks were not detected since this phase transformation required longer [ 20 , 35 ]. This result aligns with previous work [ 36 ]. The intensities of the TiC and TiB diffraction peaks increased when the starting powder composition of the TMCs did not contain 20 vol % of Ti-Al, which indicated that the volume fraction of in-situ-formed TiC and TiB were affected by the addition of Ti-Al.…”
Section: Resultssupporting
confidence: 94%
“…However, TiC and TiB diffraction peaks appeared in the diffraction patterns of TMCs consolidated at 1000 °C as shown in Figure 2 b, while the XRD patterns of TiB 2 peaks were not detected since this phase transformation required longer [ 20 , 35 ]. This result aligns with previous work [ 36 ]. The intensities of the TiC and TiB diffraction peaks increased when the starting powder composition of the TMCs did not contain 20 vol % of Ti-Al, which indicated that the volume fraction of in-situ-formed TiC and TiB were affected by the addition of Ti-Al.…”
Section: Resultssupporting
confidence: 94%
“…In recent years, researchers have made many attempts to solve the above problems. The most common method is to introduce the second phase into B 4 C ceramics, such as metallic phase (Al, Ti), oxide (Al 2 O 3 , ZrO 2 ), and boride (TiB 2 ), 6–10 to promote the densification and improve its comprehensive mechanical properties. Wang et al 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have made many attempts to solve the above problems. The most common method is to introduce the second phase into B 4 C ceramics, such as metallic phase (Al, Ti), oxide (Al 2 O 3 , ZrO 2 ), and boride (TiB 2 ), [6][7][8][9][10] to promote the densification and improve its comprehensive mechanical properties. Wang et al 11 prepared B 4 C-GNPs composites with relative density, Vickers hardness, flexural strength, and fracture toughness of 99.12%, 32.80 GPa, 508 MPa, and 4.66 MPa⋅m 1/2 respectively under the condition of 1950 • C and 30 MPa pressure for 1 h. He et al 12 used B 4 C and Ti 3 SiC 2 as raw materials to prepare B 4 C-TiB 2 composites by reactive hot pressing at 2100 • C and 25 MPa pressure, of which the flexural strength, fracture toughness, and microhardness were 592 MPa, 7.01 MPa⋅m 1/2 , and 31.00 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study of the reaction layer between the matrix and the particles is important in order to achieve a better understanding of Metals 2020, 10, 265; doi:10.3390/met10020265 www.mdpi.com/journal/metals Metals 2020, 10, 265 2 of 12 the cause that could promote or not these reactions and their products. While there is considerable literature on the grounds of strengthening and the reaction mechanisms [20,21], there are only a few studies where the reaction layer is analysed. It is also investigated how the presence of Ti x Al y as intermetallic in the titanium matrices could affect the final appearance of these secondary phases (TiB and TiC) [22][23][24]; however, the reaction layer in the presence of intermetallic, as well as its decomposition, has been little studied [25,26].…”
Section: Introductionmentioning
confidence: 99%